SOSIALISASI PENYAKIT TIDAK MENULAR (PTM) DAN PEMERIKSAAN KESEHATAN PADA KELOMPOK PENGAJIAN AL HUDA DI RT/RW 001/032 KOTA PONTIANAK - Sulastri Herdaningsih (Jurnal Buletin Al-Ribaath, 2018)
ABSTRACTAchieving the improvement of public health through a complete health care, it is necessary to joint efforts from all levels of society. In order for health status to be more equitable, it is deemed necessary to pay attention to areas / groups of people who need more health knowledge. Having previously studied the health status of Al Huda lecturers in RT / RW 001/032 Pontianak City, it is found that many who experience Non-Communicable Diseases (PTM), including, Hypertension, Diabetes Millitus, Cholesterol, and Uric Acid, so it needs to be given counseling and health checks on Hypertension, Diabetes Millitus, Cholesterol and Uric Acid. Academy of Pharmacy YARSI Pontianak as a Higher Education Institution has an important role in devoting themselves to the community contained in the Tri Darma of Higher Education Participate in improving public health status in the form of community service in the form of health socialization and health examination. After the socialization and checking of health, it was found out that the community understood Non-Communicable Disease, the community understood how to use the correct health monitoring tool, the highest prevalence of gout disease with 92% percentage. Keywords: socialization, health examination, Al Huda study